2017
DOI: 10.1371/journal.pone.0188665
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of cancer stemness by upregulating Ligand-of-Numb protein X1 in colorectal carcinoma

Abstract: Cancer stem-like cells (CSCs) have been reported to play major roles in tumorigenesis, tumor relapse, and metastasis after therapy against colorectal carcinoma (CRC). Therefore, identification of colorectal CSC regulators could provide promising targets for CRC. Ligand-of-Numb protein X1 (LNX1) is one E3 ubiquitin ligase which mediates the ubiquitination and degradation of Numb. Although several studies indicate LNX1 could be a potential suppressor of cancer diseases, the functions of LNX1 in mediating cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…A more recent study has now also implicated LNX1 in CRC [35]. Here the authors observed that LNX1 mRNA and protein were down-regulated in a population of putative cancer stem cells (side population cells) isolated from the CRC cell line HT29.…”
Section: Involvement Of Lnx1 and Lnx2 In Crcmentioning
confidence: 83%
See 2 more Smart Citations
“…A more recent study has now also implicated LNX1 in CRC [35]. Here the authors observed that LNX1 mRNA and protein were down-regulated in a population of putative cancer stem cells (side population cells) isolated from the CRC cell line HT29.…”
Section: Involvement Of Lnx1 and Lnx2 In Crcmentioning
confidence: 83%
“…The most comprehensive studies linking LNX1/2 proteins to tumorigenesis are in relation to CRC [34,35]. The human LNX2 gene maps to chromosome 13q12.2-a region that is frequently amplified in CRC.…”
Section: Involvement Of Lnx1 and Lnx2 In Crcmentioning
confidence: 99%
See 1 more Smart Citation
“…While the progression of colorectal carcinoma can be regulated by both LNX1 and LNX2, they act in opposing manners. While elevated levels of LNX2 were shown to promote the oncogenic potential of colorectal carcinoma through the maintenance of NOTCH and WNT signaling, both of which are required for cancer cell proliferation [ 87 ], LNX1 was observed to negatively regulate cancer stemness in colorectal carcinoma cells, in which LNX1 expression and CAR expression were inversely correlated, and CXADR (CAR-encoding gene) expression was shown to be inhibited upon treatment with tamoxifen, a drug frequently used in breast cancer chemotherapy [ 88 ] that stimulates LNX1 expression in the presence of estrogen receptor [ 89 ]. Contrary to expectation, Camps et al in 2013 [ 87 ] showed that LNX2 depletion reduced the levels of both NUMB and NOTCH1 proteins without affecting the levels of NUMB transcripts in SW470 (colorectal cancer cell line) cells, which was counterintuitive, considering that Lnx2 in zebrafish is commonly known to target Numb degradation [ 21 ].…”
Section: Molecular and Cellular Functions Of Lnx1 And Lnx2mentioning
confidence: 99%
“…In glioblastoma, LNX1 regulates Notch1 signaling and induces expansion of the glioma stem cell population [10]. Furthermore, several studies associated with cancer and LNX1 have suggested its role as a tumor regulator in various cancers, including gliomas and colorectal carcinoma [11,12]. LNX1 related protein, LNX2 is also reported to upregulate Wnt/beta-catenin pathway in colorectal cancers [13].…”
Section: Introductionmentioning
confidence: 99%